Perspektif Islam Dalam Mendepani Masalah Hubungan Etnik: The Islamic Perspective in Facing the Problems of Ethnic Relations - Nik Abdullah, Nik Kamaliah; Shaari, Che Zarrina (Journal Al-Muqaddimah, 2020)
Lately the world faced with various problems in particular in the context of relations between ethnic groups. Islam has a clear guideline in arranging the deal with this issue. This article displays a Islamic approach based on principles; knowledge (al-' Ilm), freedom (al-Hurriyah), met (al-Shura), justice (al-' Adalah), equations (Al-Musawah) and brotherhood, love (the spirit of wa al Mahabbah) and responsible (al-Mas'uliyyah) make society from various religious, cultural and ethnic ancestry, could be consolidated under one ummah. Appreciation of the principles of the welfare promises.